Primary motor cortex functionally contributes to language comprehension: An online rTMS study. (February 2017) - Vukovic, Nikola; Feurra, Matteo; Shpektor, Anna; Myachykov, Andriy; Shtyrov, Yury
Abstract: Among various questions pertinent to grounding human cognitive functions in a neurobiological substrate, the association between language and motor brain structures is a particularly debated one in neuroscience and psychology. While many studies support a broadly distributed model of language and semantics grounded, among other things, in the general modality-specific systems, theories disagree as to whether motor and sensory cortex activity observed during language processing is functional or epiphenomenal. Here, we assessed the role of motor areas in linguistic processing by investigating the responses of 28 healthy volunteers to different word types in semantic and lexical decision tasks, following repetitive transcranial magnetic stimulation (rTMS) of primary motor cortex. We found that early rTMS (delivered within 200 ms of word onset) produces a left-lateralised and meaning-specific change in reaction speed, slowing down behavioural responses to action-related words, and facilitating abstract words – an effect present only during semantic, but not lexical, decision. We interpret these data in light of action-perception theory of language, bolstering the claim that motor cortical areas play a functional role in language comprehension. Highlights: We tested the causal role of the motor cortex in language comprehension. Online rTMS was used to perturb left and right M1 during semantic and lexical tasks. Left M1 stimulation causally affected processing of word meaning specifically.